QUALITATIVE METHOD (CASE STUDY RESEARCH) - Santa Lusiana Sitorus (Journal Of Communication Education, 2021)
Case study is one of seven types of qualitative research that aims to increase knowledge about individual, group, social, political and other phenomena. By conducting a case study it is hoped that an understanding of the complexity of a case will be obtained and understanding its movements in a very important situation.The purpose of this paper is to understand how to make case study research by getting to know several types of case study research, understanding the procedures in case study research, the advantages and disadvantages of case study research, how to conduct case study research including making case study designs, collecting evidence, analyze the evidence obtained and finally how to make a case study research report.Keywords: Qualitative Research, Case Study Research.